Mechanisms of chromosomal evolution and its possible relation to natural history characteristics in Ancistrus catfishes (Siluriformes: Loricariidae) - Oliveira, Renildo Ribeiro de; Feldberg, Eliana; Anjos, Maeda Batista dos; Zuanon, Jansen (Journal of Fish Biology, 2009)
Ancistrus is the most speciose genus of the tribe Ancistrini, with 58 valid species and many yet to be described. Cytogenetic studies were conducted on five apparently undescribed species from the Amazon basin, which showed different diploid numbers: Ancistrus sp. Purus (2n = 34); Ancistrus sp. Macoari (2n = 46); Ancistrus sp. Dimona (2n = 52); Ancistrus sp. Vermelho (2n = 42) and Ancistrus sp. Trombetas (2n = 38). All species possessed only one pair of NOR-carrying chromosomes, but with extensive variation in both the location on the chromosome as well as in the position of the ribosomal sites on the karyotype. The karyotypic evolution of Ancistrus species seems to be based on chromosomal rearrangements, with a tendency to a reduction of the diploid number. Two new instances of XX/XY sex chromosomes for Ancistrus species, based on the heteromorphism in the male karyotype, were also recorded. The large karyotypic diversity among Ancistrus species may be related to biological and behavioural characteristics of these fish that include microhabitat preferences, territoriality and specialized reproductive tactics. These characteristics may lead to a fast rate of fixation of chromosomal mutations and eventually speciation across the basin. © 2009 The Fisheries Society of the British Isles.
Keywords: Animals; Catfish; Classification; Diploidy; Female; Genetics; Histology; Karyotyping; Male; Evolution, Molecular; Sex Chromosome; Animal; Catfishes; Diploidy; Evolution, Molecular; Female; Karyotyping; Male; Sex Chromosomes; Ancistrus; Loricariidae; Pisces; Siluriformes